2013
DOI: 10.1089/bfm.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Oropharyngeal Colostrum to Extremely Low Birth Weight Infants

Abstract: Background: Human milk reduces morbidities in extremely low birth weight (ELBW) infants. However, clinical instability often precludes ELBW infants from receiving early enteral feeds. This study compared clinical outcomes before and after implementing an oropharyngeal colostrum (COL) protocol in a cohort of inborn (born at our facility) ELBW infants. Study Design: This is a retrospective cohort study of inborn ELBW infants admitted to the Duke Intensive Care Nursery from January 2007 to September 2011. In Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 27 publications
3
68
0
11
Order By: Relevance
“…A prospective study of 15 extremely low birth weight infants demonstrated that the time to reach full enteral feeding was reduced, 15 and 1 retrospective study reported that oropharyngeal administration of colostrum resulted in starting feeding earlier and reaching birth weight sooner. 16 However, no published data have illustrated the clinical advantages of oropharyngeal colostrum administration in relation to the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A prospective study of 15 extremely low birth weight infants demonstrated that the time to reach full enteral feeding was reduced, 15 and 1 retrospective study reported that oropharyngeal administration of colostrum resulted in starting feeding earlier and reaching birth weight sooner. 16 However, no published data have illustrated the clinical advantages of oropharyngeal colostrum administration in relation to the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…19 The oropharyngeal mucosal route was recently proposed as a solution for providing maternal colostrum to the sickest infants during the early postnatal period. 11-14, 16 Rodriguez et al 12 described the expected mechanisms through which cytokines and other immunologic factors in colostrum stimulate the immature neonatal immune system via lymphoid tissues in the oropharynx and gut, resulting in the development of a protective mucosal immune barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La administración por vía orofaríngea no equivale a la administración oral, sino que consiste en colocar pequeñas cantidades de calostro (0,2 ml) directamente en la mucosa oral con la expectativa de que el líquido, o cualquiera de sus componentes, sea absorbido por la mucosa orofaríngea. Los estudios demuestran que es una práctica segura, factible y bien tolerada incluso por los bebés prematuros más pequeños (14,17). La administración orofaríngea del calostro sería considerada un complemento y no un sustituto de la nutrición enteral trófica.…”
Section: Introductionunclassified